Dacryoadenitis with multiple unilateral ocular abscesses in disseminated melioidosis - Sylves Patrick; Seah RB; Caroline B; Yap, Jin Yi; Shuaibah Ab Ghani; Hanida H (Universiti Brunei Darussalam, 2022)
Melioidosis is caused by the gram-negative bacterium Burkholderia pseudomallei and has a wide range of manifestations in many organ systems. Ocular melioidosis is a rare manifestation of Burkholderia pseudomallei that commonly presents with orbital cellulitis rather than dacryoadenitis and multiple unilateral ocular abscesses, which are uncommon. The risk of blindness in ocular melioidosis is high because this bacterium is resistant to many antibiotics, requires a longer period of treatment with antibiotics and the diagnosis is not always straightforward. Here we describe a different presentation of ocular melioidosis manifested with left preseptal abscess, orbital cellulitis with abscess and dacryoadenitis in a 50-year-old man who was treated successfully with surgery and antibiotics, along with a brief review of the literature.